PREFERENCES OF COFFEE CONSUMERS ON SERBIAN MARKET - Vlahović, Branislav; Jeločnik, Marko; Potrebić, Velibor (Economics of Agriculture, 2012)
Many citizens of Serbia consider coffee as indispensable food in daily nutrition, so nowadays drinking of coffee turns into a social phenomenon embodied in irreplaceable accomplice in almost all meetings of people. The main goal of this paper are the factors that determine demand and consumption of coffee, i.e. to gain insight in consumers preferences, motives, attitudes and interests to buy products that contain coffee in the Republic of Serbia. According to that, during 2011 was conducted market research (survey), based on previously created questionnaire. Paper also provides comparison with results obtained by similar survey in 2006 in order to notice the level of consumers attitudes move in last few years.